Dopamine pathology in schizophrenia: Analysis of total and phosphorylated tyrosine hydroxylase in the substantia nigra - PEREZ-COSTAS, EMMA; MELENDEZ-FERRO, MIGUEL; RICE, MATTHEW W.; CONLEY, ROBERT R.; ROBERTS, ROSALINDA C. (Frontiers in Psychiatry, 2012)
Despite the importance of dopamine neurotransmission in schizophrenia, very few studies have addressed anomalies in the mesencephalic dopaminergic neurons of the substantia nigra/ventral tegmental area (SN/VTA). Tyrosine hydroxylase (TH) is the rate-limiting enzyme for the production of dopamine, and a possible contributor to the anomalies in the dopaminergic neurotransmission observed in schizophrenia. In this study, we had three objectives: 1) Compare TH expression (mRNA and protein) in the SN/VTA of schizophrenia and control postmortem samples. 2) Assess the effect of antipsychotic medications on the expression of TH in the SN/VTA. 3) Examine possible regional differences in TH expression anomalies within the SN/VTA. To achieve these objectives three independent studies were conducted: 1) A pilot study to compare TH mRNA and TH protein levels in the SN/VTA of postmortem samples from schizophrenia and controls. 2) A chronic treatment study was performed in rodents to assess the effect of antipsychotic medications in TH protein levels in the SN/VTA. 3) A second postmortem study was performed to assess TH and phosphorylated TH protein levels in two types of samples: schizophrenia and control samples containing the entire rostro-caudal extent of the SN/VTA, and schizophrenia and control samples containing only mid-caudal regions of the SN/VTA. Our studies showed impairment in the dopaminergic system in schizophrenia that could be mainly (or exclusively) located in the rostral region of the SN/VTA. Our studies also showed that TH protein levels were significantly abnormal in schizophrenia, while mRNA expression levels were not affected, indicating that TH pathology in this region may occur posttranscriptionally. Lastly, our antipsychotic animal treatment study showed that TH protein levels were not significantly affected by antipsychotic treatment, indicating that these anomalies are an intrinsic pathology rather than a treatment effect.